Laparoscopic treatment of giant adnexal tumors - Sandoval Diaz, Ither (2015)
Background: The surgical management of benign large adnexal tumors has been by laparotomy because of minimally invasive surgery technical difficulties and risk of tumor malignancy. Objective: To review the experience in managing giant adnexal tumors via minimally invasive surgery with ovary or Fallopian tube anatomy preservation. Design: Retrospective and descriptive study. Setting: Specialized Gynecology Service, Hospital Nacional Edgardo Rebagliati Martins (HNERM), EsSalud, Lima, Peru. Participants: Women with large adnexal tumors. Interventions: Laparoscopy was performed in 6 patients admitted for large adnexal tumors. Main outcome measures: Characteristics and outcomes. Results: Patients average age was 35.1 years, average tumor size was 28.1 cm, and average surgical time was 75 minutes. There were no immediate post surgical complications. Conclusion: Large adnexal masses can be successfully managed with minimally invasive surgery.